Delivering Job Search Services for Unemployed People in Rural Areas: the Role of ICT - Ronald William McQuaid; Colin Lindsay (European Regional Science Association (ERSA), 2003)
The geographical remoteness of many rural communities from major centres of economic activity clearly affects the availability of public services, which tend to be concentrated in highly populated areas of industrial development. The potential benefits accruing from the use of remote, ICT-based services are therefore particularly apparent in more isolated rural communities, which are often characterised by weak physical service infrastructures. As a result, policy makers are increasingly turning to Internet and other ICT-based approaches to delivering public services. This paper discusses the potential uses of the Internet and other forms of ICT as a tool for delivering services for unemployed job seekers in rural and other areas. The analysis is based upon two distinct phases of research carried out in three areas of Scotland. The first study area is Sutherland, is a sparsely populated, remote rural `travel-to-work-area' (TTWA); the second is Wick, an adjacent remote small rural town. The third study area, `West Lothian' is a peri-urban labour market located in Scotland's `central belt', near major economic and population centres. The first phase of the research reports the results of survey work undertaken with 490 unemployed job seekers across the three areas between November 2000 and May 2001. The second phase reports the findings of twelve focus groups undertaken with job seekers in the same study areas between July and November 2002. The aim of the research was to compare the attitudes and experiences of unemployed people in these study areas regarding the use of ICT and the Internet as a means of looking for work, and to examine the impact of services for job seekers currently delivered through ICT. The research revealed that Internet-based job seeking remained of marginal importance for most unemployed people. Furthermore, a `digital divide' operated within the unemployed client group, with those most disadvantaged in terms of employability skills, educational attainment and income also unlikely to have the access, skills and awareness required to fully exploit ICT-based services. ICT-based job seeking was rather more important in remote rural communities where there were no public employment service `Jobcentre' facilities. In these areas job seekers were more likely to use the Internet as a job search tool and were particularly dependent on telephone helplines provided by the public employment service. However, respondents in rural areas also pointed to the over-riding importance of informal, social networks as a means of sharing job information in remote communities, suggesting that formal services, however they were delivered, were often by-passed by job seekers and recruiters alike. We conclude that ICT-based services may have an important role to play in the delivery of services for unemployed job seekers, especially in remote rural areas. However, policies are required to ensure that information provided through Internet and telephone-based services is locally relevant. There is also a need for community-based services to address the `digital divide' by ensuring that disadvantaged groups have access to the facilities and training they require to exploit the opportunities associated with ICT-based services. Community technology centres and locally-focused websites may allow rural job seekers to access both formal services and the informal networks that remain crucial to the job search process in remote rural areas.
Keywords: 330